2018
DOI: 10.1038/s41598-018-23521-0
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and cloxacillin combination improve antibiotic efficacy against different lifestyle of coagulase-negative Staphylococcus isolates from chronic bovine mastitis

Abstract: Bovine mastitis affects the health of dairy cows and the profitability of herds worldwide. Coagulase-negative staphylococci (CNS) are the most frequently isolated pathogens in bovine intramammary infection. Based on the wide range of antimicrobial, mucoadhesive and immunostimulant properties demonstrated by chitosan, we have evaluated therapy efficiency of chitosan incorporation to cloxacillin antibiotic as well as its effect against different bacterial lifestyles of seven CNS isolates from chronic intramammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Further research is required to evaluate the application of nanoparticles in mastitis therapy. Effect of combination of chitosan and cloxacillin on planktonic cultures, bacterial biofilms and intracellular growth in udder cells have been studied (Breser et al 2018 ). It was shown that combined approach of using chitosan and cloxacillin inhibited the formation of biofilm, improved clearance of already formed biofilm.…”
Section: Advances In Treatment Of Mastitismentioning
confidence: 99%
“…Further research is required to evaluate the application of nanoparticles in mastitis therapy. Effect of combination of chitosan and cloxacillin on planktonic cultures, bacterial biofilms and intracellular growth in udder cells have been studied (Breser et al 2018 ). It was shown that combined approach of using chitosan and cloxacillin inhibited the formation of biofilm, improved clearance of already formed biofilm.…”
Section: Advances In Treatment Of Mastitismentioning
confidence: 99%
“…Furthermore, Shi et al (2016), demonstrated that chitosan-coated iron oxide compound nanoparticles are hindering the development of biofilm biomass and declining the quantity of live bacterium. A study reported by Breser et al (2018) showed that the combination between chitosan and cloxacillin combination inhibited biofilm formation and reduced intracellular viability of coagulase-negative Staphylococcus in cases of chronic mastitis. Chakraborty et al (2010) discussed that vancomycin loaded folic acid tagged chitosan nanoparticles had a higher bactericidal effect against vancomycin-resistant S. aureus by enhancing the transport of vancomycin across bacterial cell membranes.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…For these reasons, it was included in the formulation of the polymer-based NP evaluated in this study. It has been reported that the combination of chitosan and cloxacillin potentiated the antimicrobial activity against 7 CNS isolates from chronic mastitis cases (Breser et al, 2018). Moreover, Ashraf et al (2012) found that the growth curves of 1 Escherichia coli isolate were inhibited by PHMB functionalized silver NP at lower concentrations (0.075-0.15 μg/mL) than PHMB alone (3 μg/mL).…”
Section: Staphylococcus Aureusmentioning
confidence: 95%